Natural resources rents nexus with financial development in the presence of globalization: Is the "resource curse" exist or myth?. (June 2020) - Guan, Jialin; Kirikkaleli, Dervis; Bibi, Ayesha; Zhang, Weike
Abstract: In order to promote economic activity, a country needs a productive and sound financial structure and financial development as a backbone of the economic development of the country. Our study thus aims to investigate the "resource curse" hypothesis in the presence of globalization, human capital, and economic growth in China during the period 1971–2017. Within a multivariate framework, we provide more rigorous analysis through several econometric methods, for instance, the Bayer and Hanck cointegration, the Autoregressive Distributed Lag (ARDL), robustness check by fully modified ordinary least squares (FMOLS), dynamic ordinary least squares (DOLS), canonical cointegrating regression (CCR), and Breitung-Candelon spectral Granger causality testing. Our findings show that the effect of natural resources on financial development is negative and confirm China's resources curse hypothesis, while globalization, human capital, and economic development lead to improving the financial development of the country. The causality analysis reveals that natural resources, human capital, and economic growth have a long-term relationship with financial development, while globalization short and medium-term linked with financial development. In order to promote financial sector development, our empirical outcomes have significant policy implications that highlight the need to encourage globalization and the development of human capital to ensure the effective management of natural resources. Graphical abstract: Image 1 Highlights: We explore the "resource curse" hypothesis in the presence of globalization, human capital, and economic growth in China. The Bayer and Hanck cointegration, the ARDL bounds cointegration, and robust econometrics techniques are employed. In the long-run, natural resources, human capital, and economic growth are important predictors for financial development. Globalization contributes to financial development in the medium-term and short-term.